Globalization and economic growth: a case study in a few developing countries (1980-2010) - Moghaddam, Abdolmajid Arfaei; Redzuan, Ma'rof (Sciedu Press, 2012)
The objective this study is to investigate the globalization indicators for measuring and evaluating the economic development scale. The output generated from eight selected countries revealed a fast improvement in the Gross Domestic Product (GDP) and economic growth rate. Significantly, attraction of Foreign Direct Investment (FDI) and rise of FDI as a percentage of GDP in these countries have impacted positively on foreign trade at international and regional levels. The data from these countries show that substantial growth in their economies is related unprecedented high FDI inflows. Generally, they had economic development and access to high income and as active players in the global economy.